Identification and Functional Analysis of SlitOBP11 From Spodoptera litura - Luo, Jiaojiao; Zhang, Zan; Li, Dongzhen; Liu, Jie; Li, Kun; Sun, Xiao; He, Lin (Frontiers in Physiology, 2021)
Odorant binding proteins (OBPs) play a key role in the olfactory recognition of insects, whose functions have been extensively studied in adult insects but rarely in larvae. In this study, one OBP (SlitOBP11) with high expression in larval antenna but low expression in adult antenna of Spodoptera litura was screened by RNA-seq and verified by quantitative real-time PCR. Furthermore, the function of SlitOBP11 was explored by analysis of the expression patterns and prokaryotic expression of proteins as well as assays of competitive binding. Competitive binding assay demonstrated that SlitOBP11 had high binding affinity to all four female sex pheromone components, but exhibited almost no binding affinity to plant volatiles except for a low affinity to Phenylacetaldehyde and Phenethyl acetate. Taken together, our results indicate that SlitOBP11 may be involved in the perception of female sex pheromones by S. litura larvae, and OBPs in the larvae of S. litura play an important role in the olfactory perception process. The functions of OBPs in olfaction to affect the behavioral response of Lepidoptera larvae remain to be further elucidated.